The morphological diversity of Mymaridae (Hymenoptera): an atlas of scanning electron micrographs. Part 3. Structure of the metasoma - Huber, John T.; Bolte, Klaus; Read, Jennifer D. (Zootaxa, 2024)
This is the third in a series of studies that aim to provide an overview of the morphological diversity of Mymaridae (Hymenoptera) or fairyflies, a monophyletic family of small parasitic wasps postulated as the sister group of all other Chalcidoidea. The external morphology of the metasoma of about half of the 115 currently valid described genera and subgenera is described and illustrated with about 460 scanning electron micrographs. Fifteen annotated figures of external metasoma structures and the male genitalia are included. The names of the 75 genera and subgenera illustrated, at least in part, are tabulated. An appendix lists the 23 acronyms used for morphological terms. The variety of characters and their features that could be used to help define morphologically the genera, and possibly also the species, of Mymaridae is briefly discussed.